IMPLEMENTASI DAN TANTANGAN REGULASI SERTIFIKASI HALAL DI INDONESIA (Studi Kasus Pada Sektor UMKM di Provinsi Sumatera Utara) - Batubara, Zulfa Khairina; Nawawi, Zuhrinal M; Ramadhan, Muhammad (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Halal certification is a strategic public policy instrument for strengthening the national Islamic economic ecosystem. Following the enactment of Law Number 33 of 2014 on Halal Product Assurance, the Indonesian government has intensified the mandatory implementation of halal certification, particularly for micro, small, and medium enterprises (MSMEs). Nevertheless, policy implementation at the regional level continues to face various structural, administrative, and socio-cultural challenges. This study aims to analyze the implementation of halal certification regulation for MSMEs in North Sumatra Province using a descriptive qualitative approach. The analytical framework integrates Edwards III’s policy implementation theory with the maqāṣid al-sharī‘ah perspective and Islamic economic values as articulated by Chapra and Asutay. Research data were collected through document analysis, secondary data from the Halal Product Assurance Organizing Agency (BPJPH), and exploratory interviews with three key informants, namely a regional BPJPH official, a halal facilitator (LP3H), and an MSME actor. The findings indicate that the implementation of halal certification in North Sumatra has improved significantly following the Halal Certification Facilitation Program (SEHATI). However, major constraints remain, including limited human resources, low digital literacy among MSMEs, and weak inter-institutional coordination. This study contributes theoretically by proposing an integrative maqāṣid-based halal policy implementation model and offers practical insights for strengthening Islamic public policy and halal governance at the regional level. Keywords: Halal Certification, MSMEs, Policy Implementation, Maqāṣid al-Sharī‘ah, Sharia Economics. Abstrak: Sertifikasi halal merupakan instrumen kebijakan publik strategis dalam membangun ekosistem ekonomi syariah nasional. Sejak diberlakukannya Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal, pemerintah Indonesia berupaya mendorong kewajiban sertifikasi halal, khususnya bagi sektor usaha mikro, kecil, dan menengah (UMKM). Namun, implementasi kebijakan ini masih menghadapi berbagai tantangan struktural dan kultural di tingkat daerah. Penelitian ini bertujuan menganalisis implementasi regulasi sertifikasi halal pada UMKM di Provinsi Sumatera Utara dengan menggunakan pendekatan kualitatif deskriptif. Kerangka analisis penelitian ini mengintegrasikan teori implementasi kebijakan Edwards III dengan perspektif maqāṣid al-sharī‘ah serta nilai ekonomi Islam sebagaimana dikembangkan oleh Chapra dan Asutay. Data penelitian diperoleh melalui studi dokumentasi, analisis data sekunder BPJPH, serta wawancara eksploratif dengan tiga informan kunci, yaitu pejabat BPJPH daerah, pendamping halal (LP3H), dan pelaku UMKM. Hasil penelitian menunjukkan bahwa implementasi sertifikasi halal di Sumatera Utara mengalami peningkatan signifikan pasca penerapan program Sertifikasi Halal Gratis (SEHATI), namun masih dihadapkan pada keterbatasan sumber daya, rendahnya literasi digital pelaku UMKM, dan lemahnya koordinasi lintas lembaga. Studi ini berkontribusi secara teoretis melalui pengembangan model konseptual implementasi kebijakan halal berbasis maqāṣid al-sharī‘ah serta memberikan implikasi praktis bagi penguatan kebijakan publik Islam di tingkat daerah. Kata kunci: Sertifikasi Halal, UMKM, Implementasi Kebijakan, Maqāṣid al-Sharī‘ah, Ekonomi Syariah.